The audio description: the voice promoting image in the geographical educational context - lima, Raimundo Guilherme (2020)
The paper presents an educational proposal, which aims to propose an audiovisual media production using the audio description resource. We can classify audio description as a linguistic intermediation, a mode of translation that resignifies the visual into verbal, contributing to cultural, social and educational inclusion. This time the implementation of the proposal was applied at the Nossa Senhora de Fátima Municipal School - Extremoz RN, with the 9th grade elementary school class II in the Geography subject. The methodological construction follows the following guidelines: Theoretical background about the subject, introducing ideas to students during lecture, selection of subjects, construction of scripts, filming, editing and publication of the video. In short, building an accessible audiovisual work for people with sensory disabilities (low vision or blindness). Being this audiovisual the product result of the developed experiment. Thus, the study added innovation, class engagement and construction of an educational mindset focused on the implementation of vectors that promote accessibility.